PRESCRIPTION COST ANALYSIS IN PATIENTS WITH HYPERTENSION AND TYPE 2 DIABETES MELITUS AFTER THE IMPLEMENTATION OF INDONESIAN NATIONAL HEALTH INSURANCE - Indriyati Hadi Sulistyaningrum; Arifin Santoso; Kusuma Arbianti; Garnes Mona Yulieta (Jurnal Farmasi Sains dan Praktis, 2022)
Chronic disease is a long-term health condition that requires on-going medical attention, and is classified as a non-communicable disease. The long-term medical treatment for chronic diseases, such as type 2 diabetes mellitus and hypertension is considerably costly. This study aims to determine the real cost and pattern of drug prescribing as well as the factors affecting the real Prescription Cost for hypertension and type 2 diabetes mellitus after the implementation of Indonesian National Health Insurance (JKN) as seen from the practice of Independent Physicial in collaboration with BPJS Kesehatan (Healthcare and Social Security Agency). This is a non-experimental (observational) study. The data were collected using purposive sampling method with 147 medical prescriptions as the research samples for each type of disease from the patient's medical record. Data were analyzed descriptively to determine Prescription Costs and spearman's rho test was used to determine the factors that influence Prescription Costs. The study revealed that the average Prescription Cost for type 2 DM patients was Rp17,806,- and Rp12,946 for hypertensive patients. Factors that affected Prescription Cost were diagnosis (p= 0.026), type of medicine (p= 0.000) and drug items (p= 0.000). This study concludes that patients with diabetes mellitus were treated with the drug prescription pattern of a combination of metformin and glimepiride, while patients with hypertension were provided with amlodipine. The real Prescription Cost is influenced by several factors, including; the patient's diagnosis, the type of drug given and the number of drug items provided to patients.